Analysis of rice fields change and utilization area based on spatial in Krueng Barona Jaya district regency of Aceh Besar - chairil akmal; Sugianto Sugianto; Manfarizah Manfarizah (Fakultas Pertanian, Universitas Syiah Kuala, 2016)
This study attempts to: ( 1 ) To know change rice fields and area utilization based on spatial in Krueng Barona Jaya district regency of Aceh Besar, ( 2 ) To know how the use of rice fields with the existing spatial in Krueng Barona Jaya district regency of Aceh Besar , ( 3 ) To find the factors that effecting amendment rice fields into land non farming based on spatial in Krueng Barona Jaya district regency of Aceh Besar. Study was conducted from may 2015 to May 2016 in Krueng Barona Jaya district regency of Aceh Besar and in the Laboratory Sensing Far and Cartography Faculty Agriculture Syiah Kuala University. Methods used in research is method of surveying descriptive. The result showed that any change over the function rice fields of 112,23 ha (16,11 %) change over the function the land, rice fields changing function settlement to land at 93,97 ha (13,49 %), and rice fields changed their function to of farmland dry equal to 18,26 ha (2,62 %). The results of the study also found land use there are no resemblance to 2013-2032 master of 1,14 ha a month 0,16 %. In general factors affect over the function of rice fields in Krueng Barona Jaya district their needs, demand for high land, land conditions, the urge to the conversion and the distances to the city center and near to the sub district.